Haze Pollution In Indonesia - Ariadno, Melda Kamil (Journal of Sustainable Development Law and Policy, 2025)
Haze pollution has been one of the most serious environmental catastrophes in countries with wide areas of forest, such as Indonesia. Efforts to combat haze pollution have been carried out at the national, regional and international levels. Adopting principles developed within international law arena such as sustainable development, precautionary principle, foreseeability, due diligence and good neighbourliness have been canvassed for every state in the world especially those having activities which have potential impact to cause transboundary pollution. Indonesia has been experiencing forest burns from time to time and trying to combat it ever since. National law has been developed, institutions have been designated, and mechanisms have been created. These efforts are however far from complete. Indonesia needs to go much further than what have been undertaken this far. A necessary way forward would be to ratify the 2002 Association of Southeast Asian Nations (ASEAN) Agreement on Transboundary Haze Pollution, which Indonesia fails to ratify. This paper discusses the problems of haze pollution in Indonesia, the applicable rules under international law including the state responsibility doctrine, the mechanism developed within the ASEAN Agreement, what steps have been taken by Indonesian Government in combating haze pollution, and the need for Indonesia to ratify the ASEAN Agreement.